PERAN INDIVIDUAL INNOVATION CAPABILITY, MOTIVASI INTRINSIK, DAN SELF-EFFICACY TERHADAP KINERJA INDIVIDU DALAM ORGANISASI MAHASISWA - Jessica Fiona Kimberly; Dimas Bagus Prakoso; Tommy Christian Efrata (Media Mahardhika, 2019)
The successful accomplishment of organizational goals, targets, and work programs is closely related to the organization's human resources. Any evaluation regarding organizational performance is likely to involve the accomplishment of the organization's vision, mission, and work programs. Such evaluation is conducted by the human resources within the organization. Therefore, the purpose of this research is to determine the influence of individual innovation capability, intrinsic motivation, and self-efficacy on the student organizations' individual performance at Ciputra University. Proportional random sampling is used to select 265 respondents as research samples, while Multiple Linear Regression analysis is used to analyze the research data. The results of the hypothesis tests can be summarized as follows: (1) Individual Innovation Capability significantly influences Individual Performance; (2) Intrinsic Motivation significantly influences Individual Performance; and (3) Self-efficacy significantly influences Individual Performance. The findings of this research can be used as a reference for the organization to improve the individual performances in the future